MENGHIDUPKAN KEMBALI KEGIATAN TPA SEBAGAI UPAYA PENGUATAN PENDIDIKAN KEAGAMAAN DI DESA PERSIAPAN JABDAN - Haenul Jarya; Zaitun Zahra; Muhammad Irsyad Al-Banjari; Fatrah Fatrah; Sevia Rahayu Nur Habibah; Helda Indah Sari; Mona Hayati; Rizqy Ramadhani dg.Matutu; Saparuddin Saparuddin; Yusi Nudya Rohman; Zahra Nurasyipa; Sugianor Sugianor; Redno Palupi; Moh Ibnu Faruk Fauzi; Ruslan Ruslan; Hasan Hasan (P3M STAI Sangatta, 2026)
The Qur'an Education Park (TPA) has a strategic role in shaping children's Qur'an reading skills and religious character. However, in Jabdan Preparatory Village, Muara Wahau District, East Kutai Regency, TPA activities have not run optimally due to limited educators, monotonous learning methods, and lack of learning media. This Community Service activity aims to revive TPA activities and improve the quality of religious education through assistance in learning the Qur'an and strengthening Islamic values. The methods used include assessment, planning, implementation, and evaluation through direct assistance in several landfills. Activities include guidance on reading the Qur'an, learning basic tajweed, memorizing short letters, daily prayers, and habituating Islamic morals. The results of the activity showed an increase in the enthusiasm of students, fluency in reading the Qur'an, and discipline in participating in TPA activities. Thus, this PKM contributes to strengthening the role of TPA as a non-formal religious education institution in Jabdan Preparatory Village.